Pemanfaatan Lahan Kelurahan Pejeruk Sebagai Tempat Pembudidayaan Tanaman Pangan Dan Obat Keluarga Dengan Teknik Vertikultur - Mardialina, Mala; Ramdhani, Salwah; Muliyani, Baiq I’in; Dinika, Baiq Asa; Pratiwi, Raras Aprilia; Fahira, Syarah Megianti; Harhara, Zanira Faisal; Ilhami, Dimi Frasepta; Khair, Muh. Fahrurrozi (Universitas Mataram, 2025)
The Sustainable Food Home Area (KRPL) is a community-based approach aimed at strengthening food security and improving nutritional intake through sustainable utilization of household yards. This community service program sought to develop a village-based KRPL initiative in Kebun Jeruk Neighborhood, Pejeruk Village, Ampenan District, by establishing a village seed garden and applying vertical farming techniques on limited and degraded land. The program employed an andragogical approach consisting of counseling on vertical cultivation techniques and the benefits of food and medicinal plants, hands-on training using tiered planting media, and planting simulations. The results indicate an improvement in participants’ knowledge and skills in cultivating food and medicinal plants using vertical farming methods. Furthermore, the program enhanced community awareness of the importance of sustainable and environmentally friendly food production through optimal use of household land.